Crystallisation in polymer nanocomposites - Jog, Jyoti Prakash (Materials Science and Technology, 2006)
Polymer nanocomposites are of interest as they exhibit extraordinary properties compared with the base polymer. The second phase dispersed in the polymer matrix can be carbon nanotubes, semi-conducting inorganic nanoparticles or layer silicates such as clay. Crystallisation in these materials is also of great interest. Polymers exhibit structures at various scales (e.g. lamella, unit cell and spherulites) and the presence of a second phase has a profound effect on crystallisation. General trends observed include acceleration/retardation of crystallisation, changes in spherulite morphology and, in a few cases, changes in the crystal structure. All these observations relate to the presence of a micrometre scale second phase. However, when the dimensions of the second phase are close to the chain dimensions, the effects on crystallisation become particularly interesting. An attempt is made in the present review to address the effect of a nanoscale second phase on aspects such as isothermal and non-isothermal crystallisation, spherulite growth, phase transformation and polymorphism.
Keywords: clay; crystallisation; Nanocomposites; polymer matrix composites

Polymer crystallization in the presence of ``sticky'' additives - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2009)
The effect of ``sticky'' additives (viz., those that have attractive interactions with the polymer) on polymer crystallization, has been investigated by dynamic Monte Carlo (DMC) simulations. Additive-polymer attractive interactions result in a slowing down of the polymer chain diffusivity in the melt state. Our results show that with increasing additive stickiness, polymer crystallinity decreases monotonically, and thinner crystallites form, viz., crystallization is inhibited by the presence of sticky additives. Unusually, the observed ``specific heat'' peak at the phase transition shows nonmonotonic behavior with additive stickiness, and exhibits a maximum for intermediate values of additive stickiness. While the origins of this unexpected behavior are not clear, we show that it correlates with a large interchange between crystalline and amorphous states of the monomers, in the vicinity of the additives. At this intermediate additive stickiness, we also find that crystallization follows a qualitatively different route-crystallinity shows a non-Avrami-like evolution, unlike the case at low or high additive stickiness.
Keywords: Additives; amorphous state; crystallisation; crystallites; Diffusion; Monte Carlo methods; polymer melts

Tin-silicalite-1: synthesis by dry gel conversion, characterization and catalytic performance in phenol hydroxylation reaction - Niphadkar, Prashant S.; Kotwal, Mehejabeen S.; Deshpande, Shilpa S.; Bokade, Vijay V.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2009)
Tin-silicalite-1 (Sn-MFI) has been successfully synthesized by dry gel conversion (DGC) method. The influence of various synthesis parameters such as crystallization time, temperature, water content at the bottom of autoclave, molar ratios of (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) in dry gel on the crystallization kinetics and physico-chemical properties of Sn-MFI materials has been investigated. Powder-X-ray diffraction (XRD),XPS,AAS, DRUV-vis and SEM techniques were employed as characterization tools. Time-dependent studies revealed that, the progressive crystallization of Sn-MFI depend not only on the synthesis time but also on the other various synthesis parameters. Increase in the crystallization temperature, water content at bottom of autoclave (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) molar ratios in dry gel resulted in the lowering of overall crystallization period. A good correspondence between the chemical composition of the surface and the bulk indicated the uniform distribution of Sn(4+) ions. The presence of these ions in tetrahedral coordination has been indicated by DRUV-vis spectral studies. Although, not better but comparable activity has been shown by Sn-MFI prepared by dry gel conversion method with Sn-MFI prepared by conventional hydrothermal crystallization method in the hydroxylation of phenol reaction. Increase in concentration of isolated Sn(4+) ions led to increase in phenol conversion and H(2)O(2) efficiency. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: crystallisation; Dry gel conversion; microporous materials; Sn-MFI